Hábitos de nidificação e reprodutivos da abelha coletora de óleo Centris analis (Hymenoptera - Apidae) em ninhos-armadilha sob condições tropicais - Lourenço, Diego de Vasconcelos (2018)
Pollination is a key factor in global agricultural production. Although bee management for pollination is basically done for social bees, like those of the genus Apis and the stingless bees, studies on solitary bees have been carried out in recent years, mainly in temperate regions, aiming at agricultural pollination. The solitary bee Centris (Heterocentris) analis (Fabricius, 1804) has great potential for pollination of plant species with flowers that produce oils, such as the acerola and the muricizeiro. Seeking the management of the bee in a tropical climate, it was studied all the nesting and reproductive behavior of this bee species. The study was performed from May to October of 2017, in the bee laboratory of the Federal University of Ceará, Fortaleza, State of Ceará. The experimental design consisted of 5 blocks of wood with 333 cavities, being available 287 trap nests, made in black cardboard, 12.0 cm in length and 0.5 cm in diameter. The nesting activity of the bees was monitored from 5 am to 6 pm. Data were collected on the search behavior for trap nests and their occupation, number of nests under construction and nests started each day, as well as the total number of nests each day; the number of collection trips for each floral resource; the time of trips to the field, and the incidence of parasitism and usurpation of nests. After 15 to 20 days of the nest closure, nests were placed in an incubator and daily monitored about birth of individuals and their sex and birth of parasites. After the birth of all individuals, it was measured the number of cells and the size of the brood cells and vestibular cells. The number of cells and their size were very variable. Therefore, there was influence of the number of cells on the size and the birth of males and females. Nests showed a sex ratio of 1.7♂: 1♀. The collection of resources was mostly in the early morning hours, decreasing in the later hours. The temperature had a direct relationship with the collection of pollen and nectar, as well as with the total collection of resources. Rainfall and wind speed were also directly related to plant material and pollen, respectively. The use of trap nests is a viable way of handling these bees. Their use in agricultural areas is favorable for pollination, since they nest and colonize for a long period of the year.